Collagen Nanofiber‐Lignin Composite Sponges with Adjustable Hierarchical Pore Structure for Efficient Low‐Frequency Sound Absorption - Yan Ma; Mu He; Jiaxuan Wang; Fuying Ma; Hongbo Yu; Yaxian Zhou; Shangxian Xie (Advanced Science)
Abstract Current sound‐absorbing materials, reliant on nonrenewable resources, pose sustainability and disposal challenges. This study introduces a novel collagen‐lignin sponge (CLS), a renewable biomass‐based material that combines collagen's acoustic properties with lignin's structural benefits. CLSs demonstrate high porosity (>0.97), lightweight (10 mg cm−3), and exceptional broadband noise absorption performance (sound absorption coefficient exceeding 0.9 across 2000–6300 Hz). Due to their unique hierarchical and aligned pore structure, CLSs display superior low‐frequency sound‐absorbing capabilities and a high noise‐reduction coefficient of 0.64 (for a 30‐mm‐thick sample). A geometric model is also developed to evaluate and predict the sound absorption performance with high consistency to the experimental results. Additionally, the inclusion of lignin as a green crosslinker has significantly improved the thermal stability and compressive strength by ≈600% compared to collagen sponges alone. The innovative integration of collagen and lignin in this study not only leverages the benefits of renewable resources but also presents a cost‐effective and straightforward preparation process, positioning CLS as a promising alternative for the construction of sound‐absorbing materials seeking sustainable solutions.